On the Model Checking of the SpaceWire Link Interface - Wei Hua; Xiaojuan Li; Yong Guan; Zhiping Shi; Jie Zhang; Lingling Dong (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In this paper we display a practical approach adopted for the formal verification of SpaceWire using model checking to solve state explosion. SpaceWire is a high-speed, full-duplex serial bus standard which is applied in aerospace, so its functions have a very high accuracy requirements. In order to prove the design of the SpaceWire was faithfully implements the SpaceWire protocol’s specification , we present our experience on the model checking of SpaceWire link interface using the Cadence SMV tool. We applied environment state machine to overcome state explosion and successfully  verified  a number of relevant properties about transmitter and controller of the SpaceWire in reasonable CPU time. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2001